Healthy or skinny? The negotiation between fear appeal and danmu in anorexia awareness videos - Mengsu Shi; Shuang Chen; Kexin Wang (Journal of Eating Disorders)
Abstract Background This study seeks to investigate the impact of anorexia awareness videos on the perception of anorexic figures and pro-anorexia attitude among young females, considering the employed fear appeals and the presence of pro-anorexia content in danmu, an online commenting system prevalent in China. Methods An experiment was conducted employing a 3 (Fear level of video: low, medium, high) × 4 (Danmu type: no danmu, pro-anorexia, anti-anorexia, mixed pro- and anti-anorexia) between-participants design. A total of 633 female participants were randomly assigned to view one of the twelve videos and subsequently evaluated on fear arousal, pro-anorexia attitude and perception of the anorexic figure scales. Results A moderated moderated mediation model demonstrates that heightened fear levels of anorexia awareness videos were linked to a more adverse perception of individuals with anorexia, subsequently reducing pro-anorexia attitude. Furthermore, the fear level of an anorexia awareness video, aroused fear, and the type of danmu interacted in a three-way manner regarding the perception of anorexic individuals. The presence of pro-anorexia content in danmu counteracted the observed positive impact. Conclusions These results imply that anorexia awareness videos should strive to evoke appropriate levels of fear while also addressing the potential adverse effects of pro-anorexia danmu, which may glorify anorexic bodies and undermine the intended protective outcomes.